Implementación de un sistema de optimización de procesos Run to target en la empresa Stevia One Perú SAC para llegar a la excelencia operacional - Torres Narvaez, Hilda Natali (2019)
Abstract The purpose of this research was to deploy a process optimization system, according to the run to target methodology, in the company Stevia One Perú SAC. For the execution of this investigation the design type of the research was diagnostic since it was inclined towards the evaluation of the root cause of the problem within the company Stevia One Perú SAC. starting with a fieldwork in which the facilities and the different processes were observed, the purpose was to show the most potential risks in the company in order to optimize and improve them. This process optimization system focused on delivering superior business results and a positive change in the organizational culture at each stage of its implementation. In the first part of the implementation work, a diagnosis was made with the run to target methodology to see what the company's situation was. The problems found were the lack of objectives in each area of work, lack of a well-defined organizational culture, lack of a training plan based on a diagnosis of needs. Afterwards, an action plan was executed to change the organizational culture. With this plan it was possible to train leaders of operational processes sensitized for the good execution of the system. When the implementation of the RTT system was carried out, the collaborators were trained in different topics, facilitating work tools to optimize each of their processes. A follow-up to the system was proposed and each process was controlled according to its assigned targets. The results at the management level with the implementation of this system reached a competitive advantage focused on the increase of productivity in all its processes, obtaining the reduction of the cost of stevia dry leaf from 4.6 to 2.7 $ / kg of dry leaf.